2017
DOI: 10.1038/ncomms14234
|View full text |Cite|
|
Sign up to set email alerts
|

A broadly protective therapeutic antibody against influenza B virus with two mechanisms of action

Abstract: Influenza B virus (IBV) causes annual influenza epidemics around the world. Here we use an in vivo plasmablast enrichment technique to isolate a human monoclonal antibody, 46B8 that neutralizes all IBVs tested in vitro and protects mice against lethal challenge of all IBVs tested when administered 72 h post infection. 46B8 demonstrates a superior therapeutic benefit over Tamiflu and has an additive antiviral effect in combination with Tamiflu. 46B8 binds to a conserved epitope in the vestigial esterase domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 57 publications
2
55
0
Order By: Relevance
“…The human efficacious dose of MHAB5553A is expected to be the same as that for MHAA4549A, a broadly neutralizing monoclonal IgG1 antibody that targets influenza A virus HA (25,26), based upon their similar mechanisms of action, comparable in vitro binding properties, comparable PK in mice and monkeys, and the same efficacious dose range in mouse influenza infection models (23,25,27,28). MHAA4549A also demonstrated strong antiviral activity at 3,600 mg in healthy volunteers challenged with influenza A virus (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The human efficacious dose of MHAB5553A is expected to be the same as that for MHAA4549A, a broadly neutralizing monoclonal IgG1 antibody that targets influenza A virus HA (25,26), based upon their similar mechanisms of action, comparable in vitro binding properties, comparable PK in mice and monkeys, and the same efficacious dose range in mouse influenza infection models (23,25,27,28). MHAA4549A also demonstrated strong antiviral activity at 3,600 mg in healthy volunteers challenged with influenza A virus (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this phase 1 trial, MHAB5553A, a fully human, monoclonal IgG1 antibody that targets the esterase domain of the HA globular head of influenza B virus (23), was found to be generally well tolerated in healthy volunteers following a single i.v. administration ranging from 120 mg to 10,800 mg. Tissue cross-reactivity studies have shown that MHAB5553A does not cross-react with human epitopes (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from exceeding the efficacy window of oseltamivir of 48 hours post infection, treatment with 46B8 provided better protective outcomes as compared to a 5 day oseltamivir treatment regime in IBV challenged mice. Interestingly, combinational therapy of 46B8 and oseltamivir was able to reduce IBV titres in lungs of infected mice when compared to treatments of 46B8 or oseltamivir alone [31]. Another influenza B-specific mAb CR8071 also bound to VE and showed neutralising activities in vitro and in vivo [32].…”
Section: In Vivo Studies Of Ve Binding Mabsmentioning
confidence: 98%